Low-cost internal controls for detection of Giardia cysts in water samples - Solano Barquero, Melissa (2019)
Giardia cysts stained with hot carbolfuchsin were used as internal controls in a concentration method for surface water samples. The morphological integrity of stained cysts and the stain's stability and intensity were tested with each of the chemical reagents used in the aluminum sulfate flocculation method. No alterations in morphology or color were noted. The stained cyst preparation has a low cost, high stability, and suitability for both light and immunofluorescent microscopy, making it affordable to researchers in low- and middle-income countries.